Are Leaders Born Or Made? : A Point Of View - Tri Wulida Afrianty (Universitas Muhammadiyah Jember, 2020)
shared goal by making some changes. Thus, one who influences and mobilizes others to attain their common goals can be defined as a leader. Regardless a considerable amount of literature and discussion on leadership among scholars and practitioners, there is still no agreement about where do leaders come from or who the leaders really are. Are they born or made? This question still seems to be a debatable topic.This paper presents my point of view in the matter. Based on the analysis of the five essential components of leadership in this paper, only two componentscharacter and emotional intelligencespecifically support the idea that leadership is both innate and learned. The other twocredibility and ethicsstand for leadership can be developed through learning. On the other hand, only one componenspiritualitysupports the idea that leadership is unlearned, but innate. Thus, these findings are enough to conclude that leaders are both born and made. In other words, it is my contention that leadership is ability which both inherent and can be learned.